CHEMICAL QUALITY OF MALE BALI DUCKS THAT GIVEN INDIGOFERA (Indigofera zollingeriana) LEAF EXTRACT - H., Sulfiyarma; Ariana, I N. T.; Miwada, I N. S. (Jurnal Peternakan Tropika, 2023)
The low quality of duck meat causes low consumption and production of duck meat in Indonesia.  Provision of additional feed in the form of herbal plants can improve the quality of duck meat.  This study aims to determine the effect of indigofera ( Indigofera zollingeriana ) leaf extract on the chemical quality of male bali duck meat aged 2-8 weeks.  This study used 120 male bali ducks. The research design used was a completely randomized design (CRD) which consisted of four treatments and five replications.  The treatments were drinking water without extract as a control (A), drinking water with 2% indigofera leaf extract (B), drinking water with 4% indigofera leaf extract (C) and drinking water with 6% indigofera extract (D).  The variables observed were dry matter, organic matter, crude protein and crude fat of meat.  The results showed that administration of indigofera leaf extract in drinking water at level of 2-4% significantly (P<0.05) decreased dry matter and crude protein content, and significantly (P<0.05) increased crude fat content, but had no significant effect (P>0.05) on organic matter content of meat, while administration at level of 6% significantly (P<0.05) on the control increased dry matter and crude protein content, and significantly (P<0.05) decreased crude fat content, but had no significant effect (P>0.05) on organic matter content of meat.  Based on the results of the study, it can be concluded that the administration of indigofera leaf extract ( Indigofera zollingeriana ) a level of 6% in drinking water can improve the chemical quality of male bali duck meat aged 2-8 weeks.   Keyword: Indiofera leaf extract, male bali duck, chemical quality of meat